2019
DOI: 10.3390/met9090920
|View full text |Cite
|
Sign up to set email alerts
|

Developing Improved Mechanical Property and Corrosion Resistance of Mg-9Li Alloy via Solid-Solution Treatment

Abstract: Cast Mg-9Li alloy was successfully solid-solution (SS) treated via heating at 575 °C for 4.5 h and rapidly quenched with ice-water mixture. The mechanical property and corrosion resistance of the SS alloy were simultaneously improved. Rapid bcc/hcp phase transition of the alloy occurred during the quenching process, creating the newly precipitated needle-like fine α-Mg phase, uniformly distributed in the β-Li phase matrix. Dramatic grain refinement and uniform distribution of the α-Mg phase, as well as the mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…It is apparent that the Mg-9Li alloy exhibits a typical dual-phase structure, which includes the bright lath phase and dark matrix phase. It is well known that the bright lath phase is the Mg-enriched α phase with hcp structure, which is a solution of lithium in magnesium and usually named as α-Mg phase [31]. The dark matrix phase surrounding the α-Mg phase is briefly named as β-Li phase, which is a solution of magnesium in lithium and shows a bcc structure [32].…”
Section: Microstructure Characteristicmentioning
confidence: 99%
“…It is apparent that the Mg-9Li alloy exhibits a typical dual-phase structure, which includes the bright lath phase and dark matrix phase. It is well known that the bright lath phase is the Mg-enriched α phase with hcp structure, which is a solution of lithium in magnesium and usually named as α-Mg phase [31]. The dark matrix phase surrounding the α-Mg phase is briefly named as β-Li phase, which is a solution of magnesium in lithium and shows a bcc structure [32].…”
Section: Microstructure Characteristicmentioning
confidence: 99%
“…The second group consists of contributions devoted to shaping and unconventional shaping [5][6][7]. The third group includes those articles that deal with the field of heat treatment [8][9][10][11][12][13]. Perhaps the contributions could be divided in other ways, but we consider this appropriate.…”
Section: Contribution To the Special Issuementioning
confidence: 99%
“…The mechanical property and corrosion resistance of the SS alloy were simultaneously improved. Rapid bcc/hcp phase transition of the alloy occurred during the quenching process, creating the newly precipitated needle-like fine α-Mg phase, uniformly distributed in the β-Li phase matrix [12]. The dimension quality of the strip within the hardening process is an essential parameter, which needs to be paid great attention to.…”
Section: Contribution To the Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Solution treatment of the Mg–9Li alloy at 1067 K for 4.5 h increased its yield strength from 62 to 110 MPa; the UTS increased from 100 to 120 MPa, and elongation increased from 32% to 45%. [ 15 ] Liu et al [ 16 ] used T6 state Mg–Y–Nd–Zr alloys obtained via solution and aging treatments under two different sets of conditions (T6 0 solution at 977 K for 4 h and aging at 437 K for 34 h; T6 1 solution at 968 K for 8 h and aging at 437 K for 16 h) and demonstrated that heat treatment can effectively improve the low‐cycle fatigue life of the Mg alloy. Zhang et al [ 17 ] found that aging treatment and the combination of solution and aging treatment improved the cyclic deformation resistance of hot extruded Mg–7%Zn–0.6%Zr–0.5%Y, aging treatment reduced the fatigue life of the alloy, and the combination of solid solution and aging treatment improved the alloy fatigue life under higher total applied strain amplitude; however, it reduced the low‐cycle fatigue life of the alloy under lower total applied strain amplitude.…”
Section: Introductionmentioning
confidence: 99%